Pemberdayaan UMKM Geoproduk Berbasis Speculative Design dan Gen-AI Untuk Storytelling di Desa Margacinta Pangandaran - Ayu Krishna Yuliawati; Mohamad Sapari Dwi Hadian; Rofi Rofaida; Budhi Pamungkas Gautama; Danish Febrianto Putra; Asti Nur Aryanti; Riza Saepul Millah (Jurnal Pengabdian Tri Bhakti, 2026)
Pangandaran, as one of West Java’s leading tourist destinations, possesses distinctive geodiversity and biodiversity as well as micro small and medium enterprises (MSMEs) that play a vital role in the local economy. However, competition among destinations, limited digital promotion innovation, and the underutilization of local uniqueness remain challenges for the development of geo-based products. This community service program (PkM) aimed to enhance the capacity of SMEs in Margacinta Village through training on product development and social media marketing based on speculative design with a participatory approach and Generative AI usage. The methods included needs assessment, speculative design training, digital storytelling workshops, and monitoring and evaluation. The results indicated improved knowledge and skills of SMEs in designing products rooted in geological and biological uniqueness and in utilizing social media for story-based promotion. The speculative design intervention proved effective in fostering product innovation and digital marketing strategies. Outputs included educational videos, media publications, and a replicable empowerment model for SMEs, contributing to local economic strengthening, sustainable tourism development, and the achievement of the Sustainable Development Goals (SDGs).